Encephalitozoon cuniculi infection in rabbits: An updated comprehensive review - Abd El-Ghany, Wafaa (Journal of Advanced Veterinary Research, 2026)
Encephalitozoon cuniculi (E. cuniculi) is a pervasive, obligate intracellular microsporidian parasite that represents a significant clinical challenge in domestic rabbit (Oryctolagus cuniculus) medicine. This review synthesizes current knowledge regarding encephalitozoonosis, beginning with the pathogen’s unique spore-forming biology and the high susceptibility of leporids. Transmission primarily occurs via the ingestion or inhalation of spores shed in the urine, though vertical transmission is also documented. The pathogenesis is characterized by the parasite's predilection for the central nervous system, kidneys, and ocular lenses, where it triggers chronic granulomatous inflammation. While host immunity, specifically cell-mediated responses, often keeps infections subclinical, triggers such as stress or immunosuppression can lead to overt disease. Three primary clinical manifestations: neurological syndromes (notably torticollis and ataxia), renal failure, and phacoclastic uveitis are characteristics for E. cuniculi infection in rabbits. Diagnostic challenges are a focal point of this review, as high seroprevalence in asymptomatic populations complicates the interpretation of results. The efficacy of combining quantitative serology, molecular techniques, and protein electrophoresis to achieve a definitive diagnosis are discussed. Finally, the review addresses management strategies, centering on the administration of benzimidazole anthelmintics and anti-inflammatory therapy, alongside rigorous husbandry practices. By integrating these facets, this review provides a comprehensive framework for clinicians and researchers to better understand, diagnose, and mitigate the impact of this resilient zoonotic pathogen in rabbit populations.